The multidisciplinary management of gastro-oesophageal junction tumours: European Society of Digestive Oncology (ESDO): Expert discussion and report from the 16th ESMO World Congress on Gastrointestinal Cancer, Barcelona. Issue 11 (November 2016) - Van Laethem, J.-L.; Carneiro, F.; Ducreux, M.; Messman, H.; Lordick, F.; Ilson, D.H.; Allum, W.H.; Haustermans, K.; Lepage, C.; Matysiak-Budnik, T.; Cats, A.; Schmiegel, W.; et al.
Abstract: Background and scope: The management of GOJ cancers remains controversial and may vary between countries. Evidence-based attitudes and guidelines are not easy to elaborate since most of the trials and studies reported mixed cases of oesophageal (both adenocarcinoma and squamous cell tumours), GOJ and gastric cancers. The aim of this expert discussion and position paper is to elaborate practical recommendations that integrate evidence-reported literature and experience-based attitude covering all clinical aspects of GOJ cancer across different specialities and countries in Europe. Methodology: Opinion leaders, selected on scientific merit were asked to answer to a prepared set of questions covering the approach of GOJ tumours from definition to therapeutic strategies. All answers were then discussed during a plenary session and reported here in providing a well-balanced reflection of both clinical expertise and updated evidence-based medicine. Results: Definition, classification, diagnosis and staging of GOJ tumours were updated and debated. Therapeutic aspects including endoscopic therapy, surgical management, both multimodal curative and palliative management were also reviewed for proposing practical and consensual positions and recommendations whenever possible. Conclusion: GOJ tumours deserve specific attention, not only for uniformising clinical management across countries but also for performing specific clinical and translational research, mainly in the curative perioperative setting.